The Cancer Curse: Regulatory Failure by Success - Feldman, Robin (Science and Technology Law Review, 2020)
Since the turn of the millennium, a series of regulatory decisions—unrelated in time and design—has shifted the focus of the pharmaceutical industry toward cancer research and treatment. Regulation, of course, is designed to drive public and private behavior, but the sum of these regulatory actions is driving behavior well beyond governmental design. This phenomenon represents a peculiar form of regulatory failure that cannot be sufficiently explained without contemplating a new form of regulatory failure—failure by success. As with any great epic tale, the modern saga is full of celebrities and drama, framed by truly heart-wrenching stories. However, with 89 percent of cancer deaths occurring in those older than 55 and the majority of deaths in those over age 72, this concentration of resources necessarily implicates agonizing and critical social policy decisions, ones that have remained entirely unconsidered. This article examines the regulatory history that led to this shift, ferreting out and connecting the various components for the first time. It explains the way in which this cancer curse falls outside traditional definitions of regulatory failure and should be categorized, instead, as regulatory failure by success. In addition, the article examines selected advantages and disadvantages of unintended regulatory success, along with normative questions regarding whether the cancer moonshot, as it has unfolded, is a desirable goal. In short, when engaging in a moonshot, it is best to do so with open eyes, given that flying blind is a marvelous way to crash and burn.